Gender-Responsive Strategic Policy Planning for Relocated Sex Workers: An Inclusive Public Service Governance Perspective - Pratiwi, Ryza Dani; Ximenes, Manuel (Jurnal Manajemen Pelayanan Publik, 2026)
This study examines sex worker relocation policies in Indonesia and their implications for gender-responsive policy planning, inclusive governance, and women’s socio-economic vulnerability. Although relocation is commonly framed as urban management and moral regulation, its impacts on gendered power relations and women’s post-relocation livelihoods remain underexplored. Addressing this gap, the study analyzes the design and implementation of relocation policies and their responsiveness to women’s strategic gender needs and participation. Using a qualitative phenomenological approach, data were collected in two post-relocation sites in Central Java through semi-structured interviews with relocated sex workers, vulnerable female workers, community representatives, and local government officials, supported by policy document analysis. Data were thematically analyzed using NVivo 12 Pro within Moser’s Gender-Responsive Policy Planning framework. The findings indicate that relocation policies are characterized by top-down institutional design and implementation prioritizing spatial order and short-term economic assistance, leaving women’s strategic needs, participation, and control over resources largely unmet. Consequently, women experience intensified workloads, economic insecurity, limited decision-making power, and persistent stigma. The study concludes that without gender-responsive and participatory planning, relocation risks reproduce structural vulnerability and therefore require integrated governance that prioritizes participation, gender-sensitive data systems, and institutional accountability.